Comparison of a New Neuraminidase Detection Assay with an Enzyme Immunoassay, Immunofluorescence, and Culture for Rapid Detection of Influenza A and B Viruses in Nasal Wash Specimens - Noyola, Daniel E. (American Society for Microbiology, 2000)
The performance of a new, rapid, easy-to-perform assay based on neuraminidase enzyme activity for detection of influenza virus types A and B was compared to detection by culture, indirect immunofluorescence, and enzyme immunoassay in 479 nasal wash specimens from children with respiratory infections. Compared to isolation of influenza virus by culture, the neuraminidase assay had a sensitivity of 70.1%, specificity of 92.4%, positive predictive value of 76.3%, and negative predictive value of 89.9%. There was a higher sensitivity for the detection of influenza A virus (76.4%) than for influenza B virus (40.9%). Indirect immunofluorescence showed a sensitivity of 59.8% and specificity of 97% compared to culture isolation for detection of influenza A and B viruses. Enzyme immunoassay showed a sensitivity of 89.7% and specificity of 98.1% for the detection of influenza A alone. The quality of the nasal wash specimen had a significant effect on the detection of influenza virus by all of the assays. A strong response of the neuraminidase assay was more likely to represent a culture-confirmed influenza infection. This new rapid neuraminidase assay was useful for the detection of influenza A and B viruses in nasal wash specimens.